2020
DOI: 10.33369/jkf.3.3.247-254
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan E-Modul Berbasis Hots Berbantuan Flipbook Marker Sebagai Bahan Ajar Alternatif Siswa Sma

Abstract: ABSTRAK Penelitian ini bertujuan untuk mengetahui karakteristik dan kelayakan modul yang dikembangkan  berbasis HOTS berbantuan Flipbook Marker sebagai bahan ajar alternatif siswa sekolah menengah atas.. Penelitian ini dilakukan dengan desain 4-D yang memiliki empat tahap yaitu tahap Define (Pendefinisian), Design (Perancangan), Develop (Pengembangan, dan Desseminate (Penyebaran), namun pada penelitian ini hanya dilaksanakan sampai tahap Develop. Instrumen penilaian yang digunakan dalam penelitian ini adalah l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 4 publications
3
24
0
15
Order By: Relevance
“…The developed e-module was suitable for conveying harmonic vibration material because it contains images, videos, and material explanations, making students more interested in learning rather than using textbooks. This finding is consistent with previous research, which found that the benefits of e-modules include students being pleased and interested in learning [20]. Another research found that e-modules can help with creative thinking [28].…”
Section: %supporting
confidence: 92%
See 1 more Smart Citation
“…The developed e-module was suitable for conveying harmonic vibration material because it contains images, videos, and material explanations, making students more interested in learning rather than using textbooks. This finding is consistent with previous research, which found that the benefits of e-modules include students being pleased and interested in learning [20]. Another research found that e-modules can help with creative thinking [28].…”
Section: %supporting
confidence: 92%
“…One approach to overcoming these issues is to create an appealing and functional e-module. E-modules are non-printed teaching materials that can help students learn [19] to learn actively and independently [20]. Because there are learning instructions and concepts, emodules can insert pictures or videos to help students understand teaching materials [21].…”
Section: Introductionmentioning
confidence: 99%
“…Teaching that can improve the critical thinking skills of vocational school students in overcoming environmental problems and natural disasters can be done by carrying out learning that is oriented towards increasing HOTS and HOTSEP through various learning media, learning content, learning models, and developing learning strategies (Husamah et al, 2018;Ichsan et al, 2019;Istiyono et al, 2018;. Modules and ebooks are very efficient in improving HOTS and HOTSEP abilities (Puspitasari et al, 2020;Lastuti, 2018;Rofiah et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Bahan ajar merupakan suatu bentuk yang dipergunakan di dalam melaksanakan aktivitas belajar (Puspitasari et al, 2020). Materi adalah suatu bahan yang wajib dipelajari oleh siswa menuju proses untuk belajar (Lestari, 2015).…”
Section: Pendahuluanunclassified